PRESENTATION OF INFORMATION THROUGH THE INTERNET IN SELF IN LEARNING SYSTEM SUPPORTING OPEN UNIVERSITY - Telly Joice Monalisa; Susi Wagiyati, SKom, MMSI Susi Wagiyati, SKom, MMSI (Jurnal Sistem Informasi, 2000)
Open University as a public university implemented a system of open and distance education, using media to support student self-learning poses. One of them is the internet.Internet tutorial consists of lessons on the web page, CAI (computer assisted learning), accompanied with fax facilities and internet mailing list. A total of 40 lectures were given, freely accessible via the homepage of http://www.ut.ac.id UT. due to Internet support, the view became more interesting lectures, students can learn unhindered by space and time and two-way communication between students and tutors, to be faster.